Word formation skills of Polish-English bilingual children (a study based on selected categories) - Siudzińska, Natalia (Papers in Linguistics, 2025)
The process of acquiring word formation competence in Polish by bilingual children is slower compared to their monolingual peers, especially when their second language is not Slavic. This article presents linguistic challenges faced when mastering selected word formation categories – agent nouns and place names – as regards bilingual children aged 5–9 living permanently in Ireland and concurrently learning Polish and English. This is a continuation of earlier research conducted on modification derivatives (Siudzińska 2021, 2023). Its results were instrumental in identifying differences in the linguistic development of mono- and bilingual children and showcasing techniques used by children when they are unable to form a derivative or recognize the word formation structure of a word. The level of word formation skills of bilingual children was compared with the skills of Polish-speaking children of the same age living in Poland.